Functional confirmation that the R1488* variant in SCN9A results in complete loss-of-function of Nav1.7 - Wen He; Gareth T. Young; Baohong Zhang; Peter J. Cox; Lily Ting-Yin Cho; Sally John; Sara A. Paciga; Linda S. Wood; Nicolas Danziger; Serena Scollen; Ciara Vangjeli (BMC, 2018)
Abstract Background Individuals with an extremely rare inherited condition, termed Congenital Insensitivity to Pain (CIP), do not feel pain in response to noxious stimuli. Variants in SCN9A, encoding the transmembrane voltage-gated sodium channel Nav1.7, have previously been reported in subjects with CIP accompanied by anosmia, which are typically transmitted in a recessive pattern. Functional characterisations of some of these SCN9A mutations show that they result in complete loss-of-function of Nav1.7. Methods In a consanguineous family we performed whole exome sequencing of three members who have a diagnosis of CIP and one unaffected family member. The functional effects of the segregating variant in SCN9A were determined using patch clamp electrophysiology in human embryonic kidney (HEK) 293 cells transfected with the variant. Results We found that each CIP subject was homozygous for a putatively nonsense variant, R1488*, in SCN9A. This variant was reported elsewhere in a subject with CIP, though the functional effect was not determined. Using electrophysiology, we confirm that this variant results in a complete loss-of-function of Nav1.7. Conclusions We confirm through electrophysiological analysis that this R1488* variant in SCN9A results in complete loss-of-function of Nav1.7, which is consistent with reports on other variants in this gene in subjects with CIP.